2012
DOI: 10.3390/ijms13021347
|View full text |Cite
|
Sign up to set email alerts
|

MetastamiRs: Non-Coding MicroRNAs Driving Cancer Invasion and Metastasis

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs of ~22 nucleotides that function as negative regulators of gene expression by either inhibiting translation or inducing deadenylation-dependent degradation of target transcripts. Notably, deregulation of miRNAs expression is associated with the initiation and progression of human cancers where they act as oncogenes or tumor suppressors contributing to tumorigenesis. Abnormal miRNA expression may provide potential diagnostic and prognostic tumor biomarkers and new th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 177 publications
(189 reference statements)
0
53
0
Order By: Relevance
“…miRNAs are able to regulate various biological processes, such as metabolism, differentiation, proliferation and apoptosis (4). Numerous studies have demonstrated that miRNAs are able to serve as oncogenes and tumor suppressors, and participate in the development of cancers via regulating tumor cell proliferation, differentiation, apoptosis and other biological processes by degrading mRNA or inhibiting translation of oncogenes or tumor suppressor genes (5,6). miRNAs have been demonstrated to be associated with the development and progression of cancers, and they may have potential applications as biomarkers for the diagnosis of various cancers (7).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are able to regulate various biological processes, such as metabolism, differentiation, proliferation and apoptosis (4). Numerous studies have demonstrated that miRNAs are able to serve as oncogenes and tumor suppressors, and participate in the development of cancers via regulating tumor cell proliferation, differentiation, apoptosis and other biological processes by degrading mRNA or inhibiting translation of oncogenes or tumor suppressor genes (5,6). miRNAs have been demonstrated to be associated with the development and progression of cancers, and they may have potential applications as biomarkers for the diagnosis of various cancers (7).…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies confirmed a strong association between miRNA and cancer (7)(8)(9)(10)(11). Cancer is characterized by uncontrolled cell growth, high proliferation, anti-apoptosis, acquisition of invasive properties to adjacent tissues and organs and inappropriate cell survival (12)(13)(14). Epigenetic change is crucial in tumorigenesis and miRNAs are key components of epigenetic alterations (15).…”
Section: Introductionmentioning
confidence: 99%
“…It seems that these metastamiRs regulate key steps in the metastatic program and processes, such as EMT and angiogenesis. Most commonly, metastamiRs promoting cell migration and invasion have been described [62]. Next, we will review some of the identified microRNAs with a relevant role in metastasis in human cancers.…”
Section: Mechanisms Of Invasion and Metastasismentioning
confidence: 99%
“…However, despite great advancements in the knowledge of metastasis biology, the molecular mechanisms are still not completely understood. Remarkably, a regulatory role for microRNAs in metastasis has been established, thus they have been denominated metastamiRs, as they have pro-and anti-metastatic effects [62]. The term metastamiRs was recently introduced by Welch and colleagues to refer to those regulatory microRNAs which promote or suppress various steps in migration and metastasis of cancer cells [63].…”
Section: Mechanisms Of Invasion and Metastasismentioning
confidence: 99%
See 1 more Smart Citation